2020
DOI: 10.3390/membranes10090233
|View full text |Cite
|
Sign up to set email alerts
|

Beverage–Drug Interaction: Effects of Green Tea Beverage Consumption on Atorvastatin Metabolism and Membrane Transporters in the Small Intestine and Liver of Rats

Abstract: Green tea (GT) beverages are popular worldwide and may prevent the development of many chronic diseases including cardiovascular disease and cancer. To investigate whether the consumption of a GT beverage causes drug interactions, the effects of GT beverage consumption on atorvastatin metabolism and membrane transporters were evaluated. Male rats were fed a chow diet with tap water or the GT beverage for 3 weeks. Then, the rats were given a single oral dose (10 mg/kg body weight (BW)) of atorvastatin (ATV), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Unlike LS180 cells, Caco-2 cells were deficient in moesin, which is in agreement with previous findings [45], implying a characteristic feature of LS180 cells, which carries genes for all three ERM proteins. Accumulating evidence indicates that P-gp is highly expressed not only in the cells derived from human gastrointestinal epithelium, including LS180 and Caco-2 cells [46][47][48], but also in the gastrointestinal tissues of rodents [49][50][51][52][53][54]. These previous findings strongly support the results obtained in the present study, indicating the gene expression pattern and subcellular localization of ERM along with P-gp in LS180 cells.…”
Section: Plos Onesupporting
confidence: 91%
“…Unlike LS180 cells, Caco-2 cells were deficient in moesin, which is in agreement with previous findings [45], implying a characteristic feature of LS180 cells, which carries genes for all three ERM proteins. Accumulating evidence indicates that P-gp is highly expressed not only in the cells derived from human gastrointestinal epithelium, including LS180 and Caco-2 cells [46][47][48], but also in the gastrointestinal tissues of rodents [49][50][51][52][53][54]. These previous findings strongly support the results obtained in the present study, indicating the gene expression pattern and subcellular localization of ERM along with P-gp in LS180 cells.…”
Section: Plos Onesupporting
confidence: 91%
“…Due to interspecies differences, in vitro studies have suggested variation in the degree to which tea extracts (mainly green tea) inhibit the activity of CYP1A1, CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2D6, and CYP3A4 ( 43 , 44 ). Rat models have shown reduced enzyme activity of CYP2C, CYP2E1, and CYP3A with green and black tea treatment ( 45 , 46 ), as well as increased CYP3A activity with oolong tea ingestion ( 47 ). Given the regional differences and slight changes in tea processing techniques, the results obtained in this study may differ from those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…They found intestinal CYP3A4 activity to be lowered, and hepatic CYP3A4 activity increased. OATP2 expression was decreased, which could have led to limited hepatic uptake [ 204 ].…”
Section: Assessment Of Herbal Drugs and Their Interactionsmentioning
confidence: 99%